USE OF DIFFERENT INFILTROMETERS TO ASSESS ENVIRONMENTAL DAMAGE CAUSED BY DIFFERENT LAND USES - Santos, Igor Leonardo Nascimento; Gomes Filho, Raimundo Rodrigues; Pedrotti, Alceu; Faccioli, Gregorio Guirado; Filho, Renisson Neponuceno de Araújo; Carvalho, Clayton Moura de; Assunção, Sara Julliane Ribeiro (Caminhos de Geografia, 2020)
The present work had an objective to compare the stable infiltration rate obtained by infiltrometers with reduced dimensions and varied forms in different land uses. The infiltration tests were carried out in areas planted with cowpea, crotalaria, pigeon pea and millet, as crops previous corn planting, and managed with no-tillage, minimum tillage and conventional tillage and native forest area. In order to compare and analyze the results of the stable infiltration rates obtained between the alternative infiltrometers and the considered standard, the criteria involving the standard error of estimation (EPE), the standard error of estimation adjusted (EPEa), the standard error of estimation adjusted by origin (EPEao) and coefficients of adjustments of the linear equations with their respective determination coefficients (R2) were used. It was verified that the double-ring reduced, single-ring and double square infiltrometers provided a water saving of 57.06%, 66.19% and 38.54% respectively, relative to the standard. The alternative infiltrometers overestimated the stable infiltration rate in relation to the standard. The single-ring infiltrometer obtained a stable infiltration rate correction equation that showed results very close to the standard and the best statistical indices of stable infiltration rate results were obtained by the reduced double-ring infiltrometer.